Concepção dos farmacêuticos sobre o cuidado no Brasil : análise do discurso e do conteúdo de publicações indexadas - Lima, Maria Amenildes Silva (2017)
There is a growing interest in the discussion of the care theme, among the different health areas, since the concept of care bases philosophically the professional practices of these areas. Although both health work and health care trigger a micropolitics that occurs in the encounter with the other, and although both - work in health and health care - occur in the know-how space, not all health work configures as caution, when we take into account the concept of care in its epistemological sense. Care is a polysemic concept, which in many cases has been used indiscriminately and mistakenly. Based on the assumption that the contents of the discourses reveal the professional's thinking and the epistemic foundations of his conduct, the research question arose: what is the conception of care present in the discourse of the Brazilian pharmacist? To answer this question, a qualitative research was carried out to review the state-of-the-art literature and content analysis. The general objective of this study was to perform a critical analysis of care conceptions from the perspective of Brazilian pharmacists that are described in the literature. The specific objectives of this research were: To identify and categorize the conceptions of care described in the literature; Group the conceptions of care found; Analyze the speeches. For selection of the documents, the databases of choice were LILACS and PubMed. In order to formulate the search strategy, we used the descriptors: "Pharmaceutical Care", "Pharmaceutical Care", "Pharmacy Clinic", "Pharmaceutical Clinic", "Pharmacotherapeutic Monitoring", "Pharmacotherapeutic Accompaniment", "Pharmaceutical Services" and "Clinical Services Pharmaceuticals ", to search articles published in the period from 2009 to 2016. After using filters, 34 articles were found in LILACS, among which 14 were randomly selected using the exhaustion criterion. And in the PubMed database, 44 articles were found, among which were randomly selected 06 articles by exhaustion. Through the analysis of the results of this research, it can be verified that there is a dichotomy between the discourse and the practices described in the articles, and that although many authors use a biopsychosocial conception of the man to refer to the care offered by the pharmacist, of the care presented in the articles analyzed, does not contemplate the ethical philosophical dimension of care. The academic relevance of this research is justified by the fact that it can contribute to the expansion of knowledge regarding the practices and discourses of pharmacists regarding care. This expansion of knowledge can contribute to the improvement of the practices of clinical pharmacy and pharmaceutical care, which justifies the social relevance of this research.